Preparation, transportation mechanisms and brain-targeting evaluation in vivo of a chemical delivery system exploiting the blood–cerebrospinal fluid barrier. (September 2014) - Li, Ling; Tuo, Jue; Xie, Yanqi; Huang, Meihong; Huang, Min; Pi, Rongbiao; Hu, Haiyan
Abstract In recent years, specific transportation mechanisms on the blood–brain barrier (BBB) are extensively employed for brain-targeted drug delivery via colloidal nanocarriers. However, in this study, we purposed to exploit the sodium-dependent vitamin C transporter 2 (SVCT2)-mediated transportation on the blood–cerebrospinal fluid barrier to enhance central nervous system penetration of the highly hydrophilic ibuprofen (IBU) by synthesizing a SVCT2-targeted chemical delivery system (CDS), ibuprofen-C6-O-ascorbic acid (IAA). The physicochemical parameters of IAA were determined, and the transporter-mediated transportation mechanism of IAA was explored on a BBB monolayer mode. The overall brain targeting effect of IAA was assayed on mice by measuring the biodistribution of IBU after i.v. administration and calculating the pharmacokinetic parameters and targeting indexes. Results showed that lipophilicity and solubility of IAA was conspicuously improved compared with IBU. At the physiological pH, IAA was stable while in brain homogenates it was easily degraded. Transport studies on the BBB monolayer mode revealed that IAA displayed higher transepithelial permeability than IBU via SVCT2. The biodistribution study in vivo demonstrated that the overall targeting efficiency of IAA was 1.77-fold greater than that of the IBU. In conclusion, the synthetic IAA might be a promising brain-targeted CDS for smuggling small-molecule hydrophilic pharmaceuticals into the brain.